Overweight and Obesity Status with Dental Caries among Children Aged 7–12 Years Old in Badung District, Bali 2018 - Rafitha, Hariani; Machmud, Putri Bungsu; Djuwita, Ratna; Gayatri, Dwi; Ariani Ayub, Fakhrana (Kesmas, 2019)
Dental caries is an infectious disease that Dental is characterized by the dental damage resulting from microorganism products in carbohydrate fermentation. Dental caries and obesity in children are multifactorial diseases associated with eating habits and certain lifestyle factors. This study aimed to assess the association between overweightness, obesity, and dental caries among children aged 7–12 years in Badung district, Bali province in 2018. The total sample of 426 children and their mothers were recruited from all first to fifth elementary grade students in three schools selected by simple random sampling. The logistic regression analysis has demonstrated a significant association between obesity and dental caries (OR: 1.830; 95% CI: 1.230–2.722) and showed that after controlling for the confounding variables, obese children have a twice higher chance of experiencing dental caries than non-obese children. Therefore, strengthening the existing health education programs in schools, including those on healthy food or snack components, and improving the efficiency of physical activities for preventing obesity could be a short-term strategy to protect school children from childhood obesity and dental caries.